FENOMENA PERUBAHAN DALAM PELESTARIAN BUDAYA MESATUA BALI - Pratama, I Gede Yudha (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Any change can occur when the rapid development of technology and information, which makes everything, including culture, must be able to co-exist with technology. Seeing the decline in Mesatua culture in Bali, the Mesatua tradition in Balinese society seems almost extinct. This can make a possibility for the loss of traditional culture which has cultural values that are very important for children. However, with the efforts to preserve culture through the use of digital media technology. Mesatua Bali, which was originally known as oral culture, is now becoming known as an image culture that is poured into digital media with interesting picture stories for children. To meet the data requirements used as research material, a descriptive qualitative research method is used to describe the phenomenon of change that occurs based on data collection through observation, documentation and literature study. The Mesatua Balinese culture in its preservation experiences a phenomenon of change in 3 periods, namely; oral period, writing period, and drawing period. In the phenomenon of change, each period has an impact or aspect of phenomena that causes new phenomena, changing phenomena, permanent phenomena, and even a phenomenon that is missing in the development of efforts to preserve Mesatua Bali culture.